2010
DOI: 10.1073/pnas.1012319108
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-limited retention of porous particles at density interfaces

Abstract: Downward carbon flux in the ocean is largely governed by particle settling. Most marine particles settle at low Reynolds numbers and are highly porous, yet the fluid dynamics of this regime have remained unexplored. We present results of an experimental investigation of porous particles settling through a density interface at Reynolds numbers between 0.1 and 1. We tracked 100 to 500 μm hydrogel spheres with 95.5% porosity and negligible permeability. We found that a small negative initial excess density Δρ p r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 31 publications
(40 reference statements)
3
59
0
Order By: Relevance
“…Also, due to the possibility of modelling spatial changes in permeability of the model by varying λ in space, it is possible to simulate various types and shapes of porous structures, i.e. transport through rippled sea bed (Huettel et al 1996;Kharab 1990) layered porous media or porous particles (Kindler et al 2010) which we confirmed in the flow over porous sediment scenario. …”
Section: Discussionmentioning
confidence: 61%
“…Also, due to the possibility of modelling spatial changes in permeability of the model by varying λ in space, it is possible to simulate various types and shapes of porous structures, i.e. transport through rippled sea bed (Huettel et al 1996;Kharab 1990) layered porous media or porous particles (Kindler et al 2010) which we confirmed in the flow over porous sediment scenario. …”
Section: Discussionmentioning
confidence: 61%
“…Eqs. (2−4) can be rewritten as follows: (5) This model assumes that the aggregates are nonpermeable (there is no advective flow through the aggregates), which is consistent with the suggestion that marine aggregates have very low permeability (Ploug & Passow 2007, Kindler et al 2010. Clearly, this assumption does not hold for all aggregate types in marine environments.…”
Section: Possible Mechanisms Of the Reduction Of Aggregate Settling Vmentioning
confidence: 72%
“…We also note that changes in the porosity of aggregates due to attached bacterial action have implications for the regulation of fluid exchange between interstitial spaces and the ambient water in aggregates. Kindler et al (2010) suggested that more porous aggregates can retain water for longer at density interfaces because of diffusion-limited fluid entrainment in the interstitial spaces of aggregates. Bacterial enhancement of aggregate porosity can be an important mechanism that promotes aggregate accumulation at density interfaces, a prominent phenomenon widely observed in oceanic environments (Alldredge & Gotschalk 1988, MacIntyre et al 1995.…”
Section: Implications For Materials Cycling In Marine Environmentsmentioning
confidence: 99%
“…Both of these dynamic processes of solute exchange occur at density discontinuities (pycnoclines), where aggregates are retained and form thin layers in the ocean (MacIntyre et al 1995). This process has been demonstrated in laboratory experiments on real aggregates (Li et al 2003) and porous hydrogel spheres (Kindler et al 2010), where typical marine aggregates were found to have retention times of many days at pycnoclines (Li et al 2003). During this time, the dissolved organic matter inside aggregates increases due to the lack of advection.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, the increase of DOC within the aggregates is mainly caused by the lack of advection during the residence time within a pycnocline. According to recent studies (Li et al 2003;Kindler et al 2010), these residence times (t R ) were found to follow the diffusion relaxation time as…”
Section: Effect Of a Constant Productionmentioning
confidence: 99%